Ultrastructure of the spermatozoon of the digenean Plagiorchis elegans (Rudolphi, 1802) (Plagiorchioidea, Plagiorchiidae). (30th April 2013) - Ndiaye, Papa Ibnou; Quilichini, Yann; Tkach, Vasyl V.; Greiman, Stephen E.; Bâ, Cheikh Tidiane; Marchand, Bernard
ABSTRACT The ultrastructure of the mature spermatozoon of the type genus of the Plagiorchiidae Plagiorchis elegans (Rudolphi, 1802), a parasite of the Golden hamster, Mesocricetus auratus is described. This study is the first ultrastructural study of the spermatozoon of a Plagiorchis, the second of a plagiorchiid species and only the third in the Plagiorchioidea. Previously data on spermatozoon ultrastructure existed only for the plagiorchiid Enodiotrema reductum and the omphalometrid Rubenstrema exasperatum. The mature spermatozoon of P. elegans exhibited the general pattern described in most digenean species, namely two axonemes of the 9 + "1" Trepaxonemata pattern, nucleus, mitochondria, external ornamentation of the plasma membrane, spine‐like bodies, and glycogen granules. However, the rather typical expansion of the plasma membrane is not found in P. elegans. Another peculiarity of the spermatozoon of P. elegans is the presence of a structure called thin cytoplasm termination. Spermatozoon ultrastructure of P. elegans is compared with that of E. reductum and R. exasperatum. Spermatozoon of P. elegans conforms to the general pattern described in E. reductum. Thus, this study further expands our knowledge on the spermatozoon ultrastructure among the members of the Plagiorchioidea, one of the most phylogenetically derived groups of the digenea. J. Morphol. 274:965–972, 2013. © 2013 Wiley Periodicals, Inc.